Kualiti Perkhidmatan dan Hubungannya dengan Kepuasan Pelanggan di Hospital Sultanah Bahiyah Alor Setar Perbandingan antara Pesakit Luar dan Pesakit Dalam (inpatient) - Norkhazzaina, Salahuddin (2009)
The study was carried out to investigate the relationship between service quality and customer satisfaction at Hospital Sultanah Bahiyah. The main focus of the study was to examined the relationship between service quality and customer satisfaction. The outcomes of the study are essentials in order to identify service quality factors that influence customer satisfaction in Hospital Sultanah Bahiyah. Next, the study also investigated the differences in satisfaction among the patients based on their demographic background. The research’s sample consist of two strata namely outpatient and inpatient. Furthermore, this research applied mixed-method, which combined quantitative and qualitative method to collect the data in a single study. The mixed-method was chosen to enhance opportunities for collecting the concrete and relevance data while assisting to achieve research objectives. Therefore, SERVQUAL instrument was adapted to collect quantitative data whereas structured interview was an instrument to collect qualitative data. The result of the study showed that there is a significant relationship between service quality and customer satisfaction where service quality explained about 72.4% of the variation in customer satisfaction (outpatient), and 70.3% of the variation in customer satisfaction (inpatient). However, the study indicated there are no differences in satisfaction among the patients based on demographic factors. Lastly, assurance, responsibility, and accessibility were found to be important factors in influencing customer satisfaction (outpatient) while assurance, empathy, and accessibility were able to influenced customer satisfaction for inpatient strata.